Enhancing audit procedures in accordance with the international assurance standard through the implementation of a proposed program (Journal of Accounting and Financial Studies ( JAFS ), 2023)
Abstract:                               The research seeks to identify the role of the International Assurance Standard (3402) in the auditor's procedures, as the importance of the research stems from providing assurance services for control tools through reports that are prepared according to this standard, which contribute to strengthening audit procedures through a proposed assurance program. Many conclusions were reached, the most important of which The assurance operations are considered among the operations with a special assignment, as the auditor is assigned to confirm a specific paragraph of the assurance program by the authority that assigned him. International Auditing Standard (3402) relies on two reports, the first to describe control tools and their design in service facilities, and the second to design them and their operational effectiveness to know the extent of strengths and weaknesses in the service organization, the importance of having cadres with a high scientific and practical level to carry out the task of assurance to reach those reports to the highest level of quality.